Tailored Sun Safety Messages for Outdoor Workers - Sajjad S. Fazel; Shelby Fenton; Nicole Braun; Lindsay Forsman-Phillips; D. Linn Holness; Sunil Kalia; Victoria H. Arrandale; Thomas Tenkate; Cheryl E. Peters (Elsevier, 2023)
Background: Messaging surrounding skin cancer prevention has previously focused on the general public and emphasized how or when activities should be undertaken to reduce solar ultraviolet radiation (UVR) exposure. Generic messages may not be applicable to all settings, and should be tailored to protect unique and/or highly susceptible subpopulations, such as outdoor workers. The primary objective of this study was to develop a set of tailored, practical, harm-reducing sun safety messages that will better support outdoor workers and their employers in reducing the risk of solar UVR exposure and UVR-related occupational illnesses. Methods: We adapted a core set of sun safety messages previously developed for the general population to be more applicable and actionable by outdoor workers and their employers. This study used an integrated knowledge translation approach and a modified Delphi method (which uses a survey-based consensus process) to tailor the established set of sun safety messages for use for outdoor worker populations. Results: The tailored messages were created with a consideration for what is feasible for outdoor workers, and provide users with key facts, recommendations, and tips related to preventing skin cancer, eye damage, and heat stress, specifically when working outdoors. Conclusion: The resulting tailored messages are a set of evidence-based, expert- approved, and stakeholder-workshopped messages that can be used in a variety of work settings as part of an exposure control plan for employers with outdoor workers.